Case Report: Sustained biochemical remission following early initiation of odevixibat in an infant with monoallelic ABCB11 mutation and histologically confirmed PFIC2 - Kehler, Thomas; Schaefer, Jan Thomas; Evert, Katja; Zapke, Maren; Woelfle, Joachim; Melter, Michael; Hoerning, André (Frontiers in Pediatrics, 2025)
IntroductionProgressive familial intrahepatic cholestasis (PFIC) are rare genetic hepatocellular disorders that affect bile secretion and predominantly manifest in early childhood. PFIC2, which is caused by mutations in the ABCB11 gene, often progresses to end-stage liver disease.Case presentationWe present the case of a male infant with PFIC2, which was associated with a heterozygous frameshift mutation in the ABCB11 gene as well as an additional heterozygous variant in the ATP8B1 gene. Initial clinical management involved ursodeoxycholic acid (UDCA) administration and fat-soluble vitamin supplementation. However, it was only after switching treatment to the ileal bile acid transporter (IBAT) inhibitor odevixibat at three months of age, that the patient exhibited significant improvement, including normalization of cholestasis parameters and liver enzymes. Liver function has remained stable on therapy for 2.5 years during which time the patient has maintained normal growth and development with no evidence of disease progression.DiscussionThis case study highlights the effectiveness of odevixibat in managing PFIC2, demonstrating sustained disease suppression and symptomatic relief. It also emphasizes the importance of comprehensive clinical evaluation and accurate disease characterization as well as the potential of targeted therapies in improving outcomes for patients with PFIC2.